Analisis Spasial Lokal Faktor Risiko Individu terhadap Kejadian ISPA Balita di Kecamatan Kebon Jeruk Wilayah - Davina Afifah Zahra; Witri Zuama Qomarania; Hosizah Hosizah; Tria Saras Pertiwi; Mieke Nurmalasari (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Prevalence of acute respiratory infections (ARI) in Indonesia among toddlers in 2024 was 52.7%, with West Jakarta Administrative City ranking second highest in DKI Jakarta Province. ARI is an upper respiratory tract infection influenced by infectious agents and various individual and environmental risk factors. Differences in risk factors have the potential to cause differences in ARI incidence between regions, requiring spatial analysis to identify the geographical correlation of disease incidence. This study aims to analyze the spatial correlation of ARI incidence in toddlers with risk factors between sub districts in the Kebon Jeruk Health Center working area in 2025. The study was conducted from August - September 2025, with a population of 16,344 children with ISPA and a sample of 109 children. Analyzed using Moran's I Global Index and Local Indicators of Spatial Association (LISA) using the GeoDa program. The global analysis revealed no spatial autocorrelation between the occurrence of ISPA in children and all the risk factors studied. However, local spatial analysis identified significant spatial autocorrelation between ISPA cases and the following risk factors incomplete immunization (p-value = 0,015) in Kebon Jeruk subdistrict, smoking habits of family members (p-value = 0,015) in Kedoya Selatan and Sukabumi Selatan subdistrict, and mother education level (p-value = 0,006) in Kelapa dua subdistrict.